Diagnostics in Venous Thromboembolism: From Origin to Future Prospects - Lippi, Giuseppe; Danese, Elisa; Favaloro, Emmanuel J.; Montagnana, Martina; Franchini, Massimo (Seminars in Thrombosis and Hemostasis, 2015)
Venous thromboembolism (VTE) is a prevalent and life-threatening condition that requires an accurate and timely diagnosis. The current diagnostic approach to this condition, entailing an efficient integration of clinical judgment, diagnostic imaging, and laboratory testing, is the result of decades of scientific and medical research. This article aims to present and discuss the major breakthroughs that have occurred in the diagnostic imaging of both deep vein thrombosis and pulmonary embolism, along with the various biological markers that have emerged from the laboratory bench and which have only marginally migrated to the bedside. Despite decades of research, the current diagnostic armamentarium for an efficient diagnosis of VTE remains suboptimal, and some wiggle room remains for the development of more efficient diagnostic tools, which may include thrombus-targeted molecular imaging, infrared thermal imaging, thrombin generation, and proteomics.
Keywords: venous thromboembolism; deep vein thrombosis; pulmonary embolism; diagnosis; D-dimer